Risks to birds traded for African traditional medicine: a quantitative assessment - Vivienne, L Williams (Public Library of Science (PLoS), 2018)
Few regional or continent-wide assessments of bird use for traditional medicine have been attempted anywhere in the world. Africa has the highest known diversity of bird species used for this purpose. This study assesses the vulnerability of 354 bird species used for traditional medicine in 25 African countries, from 205 genera, 70 families, and 25 orders. The orders most represented were Passeriformes (107 species), Falconiformes (45 species), and Coraciiformes (24 species), and the families Accipitridae (37 species), Ardeidae (15 species), and Bucerotidae (12 species). The Barn owl (Tyto alba) was the most widely sold species (seven countries). The similarity of avifaunal orders traded is high (analogous to "morphospecies", and using Sørensen's index), which suggests opportunities for a common understanding of cultural factors driving demand. The highest similarity was between bird orders sold in markets of Benin vs. Burkina Faso (90%), but even bird orders sold in two geographically separated countries (Benin vs. South Africa and Nigeria vs. South Africa) were 87% and 81% similar, respectively. Rabinowitz's "7 forms of rarity" model, used to group species according to commonness or rarity, indicated that 24% of traded bird species are very common, locally abundant in several habitats, and occur over a large geographical area, but 10% are rare, occur in low numbers in specific habitats, and over a small geographical area. The order with the highest proportion of rare species was the Musophagiformes. An analysis of species mass (as a proxy for size) indicated that large and/or conspicuous species tend to be targeted by harvesters for the traditional medicine trade. Furthermore, based on cluster analyses for species groups of similar risk, vultures, hornbills, and other large avifauna, such as bustards, are most threatened by selective harvesting and should be prioritised for conservation action.